Monotonic behaviour of post-installed mechanical anchors installed in prestressed concrete hollow-core floor units. (October 2020) - Del Rey Castillo, E.; Ingham, J.
Abstract: Post-installed anchors are used to connect structural and non-structural elements to the main concrete structure. Extensive research has been published on the behaviour of these anchor for various seismic loads and substrate conditions. However, the behaviour of post-installed anchors in prestressed concrete hollow-core floors is still largely unknown, despite several guidelines and acceptance criteria being published and manufacturers having qualified products available. The shallow concrete cover in the hollow regions compromises both the tensile and the shear behaviour of anchors installed in these regions, as acknowledge in international standard. The behaviour of anchors installed in the web regions can be assimilated to the behaviour of anchors installed in solid concrete, but the installation process can damage the prestressing strands. Additionally, it is not always possible for the installer to establish where the web regions or the hollow regions are. The behaviour of four types of anchors for non-structural applications was investigated, both in tension and shear loading conditions. The failure modes of the anchors were compared, in addition to the peak load, the displacement at peak load and the stiffness. The coefficient of variation was also included in the discussion. Anchors that were designed to be embedded deeper than the cover thickness in the hollow region exhibited a significant performance reduction (up to 35%). Anchors that were specifically designed to be installed in the hollow region performed poorly when installed in the web region. This behaviour was expected because the anchors were installed without complying with the instructions from the manufacturer, but justified as proper installation in the correct region cannot be guaranteed. Anchors that were embedded less than the thickness of the concrete cover in the hollow region did not experience any performance reduction. The recommendation was therefore to always use anchors assessed and approved for use in hollow core applications, considering that anchors that are shallower than the concrete cover in the hollow regions can help to mitigate the risks of improper installation.